An analysis of the implementation of murabaha, mudharabah, and musyarakah contracts in the financial management of Al Hidayat Gerning Islamic boarding school - Ahmad Zainur Rozikin; Selly Puspita Sari (Indonesia Accounting Research Journal, 2025)
This study aimed to analyze the implementation of Murabaha, Mudharabah, and Musyarakah contracts in the financial management of Al Hidayat Gerning Islamic Boarding School, Pesawaran, Lampung. The research employed a qualitative method with a case study approach. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that the three contracts had been applied in various economic activities of the pesantren, such as procurement of goods, management of student-run businesses, and collaborations with external parties. The application of these Sharia contracts contributed to enhancing the pesantren’s economic independence, providing practical Sharia economic learning for students, and increasing public trust. Challenges included limited human resources with expertise in Islamic finance and a manual recording system. The pesantren addressed these challenges through internal training, cooperation with external institutions, and the adoption of digital financial recording. The study recommends strengthening the competencies of Sharia financial managers and developing technology-based financial management systems to achieve more effective and sustainable financial practices.